Locating Religions : Contact, Diversity, and Translocality. - Glei, Reinhold F. (Dynamics in the History of Religions, 2016)
This collection of articles is an innovative contribution to religious studies, because it picks up concepts developed in the wake of the so-called "spatial turn". Religions are always located in a certain cultural and spatial environment, but often tend to locate (or translocate) themselves beyond that original setting. Also, many religious traditions are not only tied to or associated with the area its respective adherent live in, but are in fact "bi-local" or even "multi-local", as they closely relate to various spatial centers or plains at once. This spatial diversity inherent to many religions is a corollary to religious diversity or plurality that merits in-depth research. The articles in this volume present important findings from a series of settings within and between Asia and Europe